Discounting disentangled - Moritz A. Drupp; Mark C. Freeman; Benjamin Groom; Frikk Nesje (University of Oslo, Department of Economics, 2015)
As the most important driver of long-term project evaluation, from climate change policy to infrastructure investments, the social discount rate (SDR) has been subject to heated debate among economists. To uncover the extent and sources of disagreement, we report the results of a survey of over 200 experts that disentangles the long-term SDR into its component parts: the pure rate of time preference, the wealth effect, and the real risk-free interest rate. The mean recommended SDR is 2.27 percent, with a range from 0 to 10 percent. Despite disagreement on point values, more than three-quarters of experts are comfortable with the median SDR of 2 percent, and over 90 percent find an SDR in the range of 1 to 3 percent acceptable. Our disentangled data reveal that only a minority of responses are consistent with the Ramsey Rule, the theoretical framework dominating discounting policy. Instead, experts recommend that governmental discounting guidance should be updated to deal with uncertainty, relative prices, and alternative ethical approaches.
Keywords: H43; D61; Q58; 330; Social discount rate; project appraisal; expert opinions; disagreement